STRATEGI PENINGKATAN EFISIENSI PEMASARAN SAPI POTONG PADA KELOMPOK PETERNAK SAPI “MEKAR JAYA” DI DESA PUHU-PAYANGAN - Sukanata I W; N. Suparta; K.W. Parimartha; I W. Budiartha; Suciani - (Buletin Udayana Mengabdi, 2013)
The members of cattle farmer groups “Mekar Jaya” are small farmers who raise 2-5 heads of cattle. Marketingsystem has not yet been well-organized, the role of the group is not maximized in assisting its members to marketthe cattle produced. The farmers marketed their cattle individually by selling to the middleman known as “belantik”who come to the farm location. The price paid by the belantik was determined based on estimated weight ofcattle, in which the skill of farmers in this case was not adequate. The market structure faced by farmers leads tomonopsony, market chain was too long, and farmers’ bargaining position was weak. The above conditions caused tolow farmer’s share, it was only 63.48%. This Community service aims to improve the efficiency of cattle marketingin this group so that the farmer’s share could be increased. The methods used were a lecture, discussion, andpractice. This activity provided a positive influence on changes in mindset and behavior of members of the groupin the cattle marketing. These changes included: increasing the role of the group to support the marketing, marketchain was shorter, and upgrading the skills of farmers to estimate the cattle weight. These changes improvedmarketing efficiency showed by the increase in farmer’s share of 5.55%. The increasing of farmer’s share was stillfelt not maximized because there was cheating indication in weighing cattle in livestock market.